DIMENSI ETIKA DAN FILOSOFI PENDIDIKAN DALAM PEMANFAATAN ARTIFICIAL INTELLEGENCE DI UPT SPF SDN TAMAMAUNG I KOTA MAKASSAR - Fina Melani Putri; Widya Afriani; Eka Melisa; Nurna Ningsih; Burhan; Nurwidyayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence in elementary education presents both opportunities and challenges, particularly because its use is not only related to learning effectiveness but also concerns the development of students’ character, learning ethics, and humanistic values. This study aims to describe and understand the ethical dimensions and educational philosophy underlying the utilization of Artificial Intelligence at UPT SPF SDN Tamamaung I. This research employed a qualitative approach with a phenomenological design, as it focused on the experiences, perspectives, and interpretations of participants regarding the use of Artificial Intelligence in the context of elementary education. The research subjects were selected purposively, consisting of the principal and teachers who possessed experience or knowledge related to the implementation of Artificial Intelligence in teaching and learning activities. Data collection techniques included in-depth interviews, observations, and documentation, while the data were analyzed using phenomenological analysis through meaning categorization, identification of essential themes, and interpretation of the core experiences of the participants. The findings revealed that Artificial Intelligence is perceived as a supportive learning tool that can assist teachers in searching for information, developing teaching materials, and enriching instructional variations. However, its implementation also raises ethical concerns, such as the potential for student dependency, decreased learning autonomy, issues of academic honesty, and the protection of personal data. From the perspective of educational philosophy, Artificial Intelligence is not viewed as a replacement for teachers, but rather as a tool that must be utilized selectively, responsibly, and consistently oriented toward character building, human values, and pedagogical relationships. Therefore, the use of Artificial Intelligence in elementary schools should be guided through teacher supervision and clear school policies to ensure alignment with the humanistic goals of education.